2021
DOI: 10.3389/fgene.2021.761728
|View full text |Cite
|
Sign up to set email alerts
|

Review: Balancing Selection for Deleterious Alleles in Livestock

Abstract: Harmful alleles can be under balancing selection due to an interplay of artificial selection for the variant in heterozygotes and purifying selection against the variant in homozygotes. These pleiotropic variants can remain at moderate to high frequency expressing an advantage for favorable traits in heterozygotes, while harmful in homozygotes. The impact on the population and selection strength depends on the consequence of the variant both in heterozygotes and homozygotes. The deleterious phenotype expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…It is thus unlikely that selective advantage explains the observed DHH frequencies, or the rapid increase in MTRDHH3 frequency between 2017 and 2018. However, many examples of balancing selection for deleterious alleles have been described in livestock [52]. For example in sheep, a missense variant in FGFR3 was associated with enhanced skeletal growth and meat yield when heterozygous while it induced chondrodysplasia (spider lamb syndrome) when homozygous (OMIA 001703-9940) [53].…”
Section: Discussionmentioning
confidence: 99%
“…It is thus unlikely that selective advantage explains the observed DHH frequencies, or the rapid increase in MTRDHH3 frequency between 2017 and 2018. However, many examples of balancing selection for deleterious alleles have been described in livestock [52]. For example in sheep, a missense variant in FGFR3 was associated with enhanced skeletal growth and meat yield when heterozygous while it induced chondrodysplasia (spider lamb syndrome) when homozygous (OMIA 001703-9940) [53].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that horned individuals were homozygous for the absence of the insertion, whereas polled individuals were homozygous for its presence. It has been speculated that when the EEF1A1-like insertion is present, EEF1A1 transcripts bind to the 3′-UTR of the RXFP2 mRNA, leading to post-transcriptional downregulation [ 56 , 57 ]. In Bündner Oberländer sheep with both polled and horned phenotypes, horned individuals were homozygous for the absence of the insertion; however, two polled individuals were found to be heterozygous for the insertion.…”
Section: Main Textmentioning
confidence: 99%
“…Usually, these types of harmful alleles are eliminated from the population by selection, which can be effective for dominant harmful alleles that reduce the fitness of heterozygous animals. Nevertheless, due to the low frequency, recessive harmful alleles are usually masked from natural selection by a dominant harmless allele and therefore easily transmitted to the next generation [4]. This effect is called balancing selection.…”
Section: Introductionmentioning
confidence: 99%